Evaluación de eugenol (extracto del clavo de olor) como profilaxis de la carga bacteriana bucal en equinos en la parroquia de Machachi canton Mejía - Gutiérrez Camacho, Franklin Misael (2015)
This research was done in the Pichincha Province, Mejia Canton, in El Porvenir Estate, which lasted 15 days, the objective was to evaluate eugenol as prophylaxis of oral bacterial load in horses, the study consists of two treatments: First treatment (application of 1% eugenol) cleaning every 48 hours, Second treatment (application of water washing and brushing) is performed cleaning is performed every 48 hours and decreasing loads swabs were evaluated of oral mucosa (CFU / ml). In the first sampling without any treatment, for first treatment the average was 420714.29 colony forming units (CFU) and second treatment was obtained 362,857.14 colony forming units (CFU), then the five washed and end of treatment for first treatment the average was 44842.86 colony forming units (CFU) and second treatment was obtained 3732, 86 colony forming units (CFU). At the end of the application of the two treatments, Student t- technique in which it indicates that both treatments lower the bacterial load being more efficient water washing and brushing was used....